2009
DOI: 10.1002/cbic.200900510
|View full text |Cite
|
Sign up to set email alerts
|

The Global Virulence Regulators VsrAD and PhcA Control Secondary Metabolism in the Plant Pathogen Ralstonia solanacearum

Abstract: Die Anwendung der Metathese, besonders der Ringschlussmetathese (RCM) zur Bildung von Fünf‐ und Sechsringen, ist heute in der organischen Chemie weit verbreitet; dennoch gibt es überraschend wenige Beispiele für ihre Anwendung zur Synthese aromatischer Verbindungen. Deren Bedeutung in der medizinischen Chemie und der Naturstoffsynthese, verbunden mit der Wirksamkeit von RCM‐Katalysatoren und ihrer Toleranz gegenüber funktionellen Gruppen, gibt Anlass, die Anwendung der RCM in der Arensynthese zu untersuchen. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 87 publications
1
41
0
Order By: Relevance
“…In addition, HrpGcontrolled functions can also be activated via HrpG post-transcriptional modification, as well as via activation of hrpB transcription by an unidentified environmental metabolic signal(s) perceived in minimal culture medium (Genin et al, 1992;Brito et al, 1999;Plener et al, 2010). Beside HrpG, the sensor histidine kinase VsrA controls many other virulence functions (Schell et al, 1994;Huang et al, 1995;Schneider et al, 2009;Meng et al, 2011). In a previous study we showed that a hrpG stop mutation allowed the chimeric Ralstonia to infect nodule cells, via the modulation of T3SS-independent HrpG-controlled functions (Marchetti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HrpGcontrolled functions can also be activated via HrpG post-transcriptional modification, as well as via activation of hrpB transcription by an unidentified environmental metabolic signal(s) perceived in minimal culture medium (Genin et al, 1992;Brito et al, 1999;Plener et al, 2010). Beside HrpG, the sensor histidine kinase VsrA controls many other virulence functions (Schell et al, 1994;Huang et al, 1995;Schneider et al, 2009;Meng et al, 2011). In a previous study we showed that a hrpG stop mutation allowed the chimeric Ralstonia to infect nodule cells, via the modulation of T3SS-independent HrpG-controlled functions (Marchetti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The production of transaminase and furanone synthase, which are encoded by ralD and ralA , respectively, depends on functional PhcA via the phc QS system. Both the transaminase and furanone synthase are involved in the biosynthesis of ralfuranone I (Schneider et al, 2009; Wackler et al, 2011; Kai et al, 2014). Ralfuranone I is non-enzymatically converted into ralfuranone B in the supernatant (Kai et al, 2016).…”
Section: Feedback Regulation Of the Phc Qs By Ralfuranonesmentioning
confidence: 99%
“…Therefore, the integrated regulation of vsrAD and vsrBC expression by ralfuranones A, B, and J contributes to EPS I production and swimming motility. Furthermore, VsrAD is upstream of PhcA and is involved in the biosynthesis of ralfuranones (Schneider et al, 2009). Therefore, the expression of vsrAD may be feedback-regulated through ralfuranones A, B, and J, leading to the regulation of PhcA function.…”
Section: Regulation Of the Two-component Systems Vsrad And Vsrbc Bymentioning
confidence: 99%
“…From a biosynthetic perspective, micacocidin represents a new and discrete natural product class made by R. solanacearum and expands the known metabolome of this species, which already includes staphyloferrin B (3), the HrpBdependent factor HDF (8), and the ralfuranone family of compounds (37). It is worth mentioning that the availability of the genome sequence of GMI1000 (33) not only was instrumental in the discovery of these metabolites by promoting the development of specific isolation strategies but also granted insights into their biosyntheses (8,42).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding its significance as a pathogen, we know surprisingly little about the secondary metabolome of this bacterium and the ensuing implications for virulence. Recent studies have shown that R. solanacearum is capable of natural product biosynthesis and that the expression of the required biosynthesis genes responds to virulence-associated regulators (8,37), assuming a role of secondary metabolites in host adaptation and/or pathogenesis.…”
mentioning
confidence: 99%